Galaxy clusters at 0.6 < z < 1.4 in the UKIDSS Ultra Deep Survey Early Data Release - Breukelen, C; Clewley, L; Bonfield, D; Rawlings, S; Jarvis, M; Barr, J; Foucaud, S; Almaini, O; Cirasuolo, M; Dalton, G; Dunlop, J; Edge, A; et al. (2006)
We present the first cluster catalogue extracted from the UKIRT Infrared Deep Sky Survey Early Data Release. The catalogue is created using UKIDSS Ultra Deep Survey infrared J and K data combined with 3.6 micro-m and 4.5 micro-m Spitzer bands and optical BVRi'z' imaging from the Subaru Telescope over 0.5 square degrees in the Subaru XMM-Newton Deep Field. We have created a new cluster-detection algorithm, based on the Friends-Of-Friends and Voronoi Tessellation methods, which utilises probability distribution functions derived from a photometric redshift analysis. We employ mock catalogues to understand the selection effects and contamination associated with the algorithm. The cluster catalogue contains 13 clusters at redshifts 0.61 <= z <= 1.39 with luminosities 10 L* <~ L_tot <~ 50 L*, corresponding to masses 5 x 10^13 M_sun <~ M_cluster <~ 3 x 10^14 M_sun for (M/M_sun) / (L/L_sun) = 75h. The measured sky surface density of ~ 10 deg^-2 for high-redshift (z=0.5-1.5), massive (>10^14 M_sun) clusters is precisely in line with theoretical predictions presented by Kneissl et al. (2001).